Between Religious Guidance and Shariah Legal Reform: Rethinking Indonesia’s Premarital Guidance for School-Age Adolescents (BRUS) program - Nadhrah, Fatiya; Abd. Mukhsin; Hashemi , Shoaleh (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: Early marriage continues to be a prevalent issue in Indonesia, notwithstanding the Ministry of Religious Affairs' implementation of the Premarital Guidance for School-Age Adolescents (BRUS) program. The deficiency of legal understanding among youngsters, inadequate communication tactics, and feeble institutional coordination hinder the program's efficacy Purpose: to evaluate the implementation of BRUS at KUA Rambutan, analyzing its effects on legal knowledge and the prevention of early marriage, while also identifying policy and structural deficiencies Methods: This study employed an empirical legal research methodology, gathering primary data via interviews with KUA officials and adolescents involved in the BRUS program. Secondary data were acquired from law papers, policy reports, and scholarly literature. The data were examined through the lenses of Legal Communication Dysfunction Theory and Legal Responsiveness Theory to assess the deficiencies in BRUS implementation Results: The findings demonstrate that BRUS has a negligible effect on decreasing underage marriage rates, attributed to inadequate communication between KUA and adolescents, insufficient youth-oriented outreach initiatives, and the lack of legal enforcement measures. Implication: This study enhances legal awareness and policy evaluation research by illustrating the necessity for religious institutions to align their programs with legal and social frameworks for efficacy. It proposes integrating Maslahah evaluations into judicial rulings on marital dispensations, improving multisectoral cooperation, and updating BRUS communication techniques Originality: This research offers a comparative analysis between Indonesia and Algeria, illustrating how an integrated approach that combines religious counseling, legal enforcement, and community engagement can markedly enhance premarital education and mitigate underage marriage